Plot Analysis and Social Commentary in Nadine Labaki’s Capernaum (2018) - Risa Laurie Mawardi; Aby Mutiara Wulandari; Marina Sisilia; Denisa Laula Anbiya (Paradigma Lingua, 2024)
The plot structure plays a pivotal role in a film’s success, effectively guiding the audience through its narrative. As defined by Stanton (2007, p. 22), a plot is a series of interconnected events where each incident causes another, creating a cohesive storyline. This cause-and-effect dynamic significantly enhances a film’s engagement and emotional impact. One film that exemplifies this well-structured approach is Nadine Labaki’s Capernaum (2018). The film tells the heart-wrenching story of Zain, a boy who escapes from his abusive parents and sues them for bringing him into a world of misery. “Capernaum” has received critical acclaim, winning numerous awards, including the Jury Prize at the 2018 Cannes Film Festival. This study uses Tasrif’s theory, as cited in Nurgiyantoro (2013), to examine the film’s plot stages. Through a qualitative descriptive method, employing a narrative structure approach, the analysis focuses on the progression of events in the film. The data consists of dialogues, scenes, and imagery from Capernaum. The findings of this research outline five major plot stages: (1) the introduction of the situation, (2) the emergence of conflict, (3) the rising action, (4) the climax, and (5) the resolution. Each of these stages is examined to reveal how Capernaum underscores the systemic failures in protecting vulnerable children, serving not only as a powerful narrative but also as a compelling social commentary.